Results of the XVI Сongress of Anthropologists and Ethnologists of Russia: Perm, July 2-6, 2025 - Сhernykh A.V.; Kamenskikh, M.S. (Perm Federal Research Centre Journal, 2025)
The article describes the preparation and holding of the XVI Congress of Anthropologists and Ethnologists of Russia on July 2-6, 2025. The Congress became the largest scientific event in the region in 2025. It involved more than 1500 participants selected for the program. The scientific discussion was conducted at 2 plenary, 62 sectional workshops and 7 round tables. The article examines the topics of issues discussed at the scientific forum, the composition of the participants, the history of the Congress and the program for its holding in Perm. The Appendix contains materials from a press conference attended by prominent Russian researchers.